2015
DOI: 10.1007/s11340-015-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Shear-Compression Specimen for Large Strain Testing

Abstract: A modified shear-compression specimen (SCS), for large strain testing over a wide range of strain rates is presented. The original SCS design includes two rectangular slots that are machined at 45°with respect to the longitudinal axis. The modification consists of creating two diametrically opposed semi-circular slots. The new "circular" specimen is first thoroughly investigated numerically under quasi-static and dynamic loading using an elastoplastic material model. The results of the comparison between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 27 publications
0
36
2
Order By: Relevance
“…The stress-strain curve significantly differs between cylindrical specimens and SCS. By contrast, previous works on rolled steel reported that consistent results between SCS and cylindrical specimens [5,6,18]. In the present study, the material yield at strain is approximately 0.05 for cylindrical specimens and 0.3 for SCS.…”
Section: Comparison Between Cylindrical Specimens and Scscontrasting
confidence: 94%
See 1 more Smart Citation
“…The stress-strain curve significantly differs between cylindrical specimens and SCS. By contrast, previous works on rolled steel reported that consistent results between SCS and cylindrical specimens [5,6,18]. In the present study, the material yield at strain is approximately 0.05 for cylindrical specimens and 0.3 for SCS.…”
Section: Comparison Between Cylindrical Specimens and Scscontrasting
confidence: 94%
“…This study presented the relationship of equivalent stress to applied load and the constants required by the test. To eliminate stress concentration in the fillet regions of the gauge section, Dorogoy et al [6]. developed SCS geometry by using two diametrically opposed semi-circular slots (instead of rectangular).…”
Section: Introductionmentioning
confidence: 99%
“…The failure patterns of the STS specimens is different from that of an SCS specimen [28,30]. In the STS, a crack initiates at the center of the gauge and propagates toward its ends, while in SCS specimen the opposite happens, namely the crack starts at the ends and propagates towards the center.…”
Section: Numerical Resultsmentioning
confidence: 93%
“…The specimen is similar to the known shear compression specimen (SCS) which was introduced in [16] and was validated numerically for static and dynamic loading and parabolic hardening materials in [17][18][19]. The SCS was used in several investigations [20][21][22][23][24][25][26][27] and was recently modified to have a circular gauge [28]. The STS consists of a long cylinder having an inclined gage section created by two diametrically opposed semi-circular slots which are machined at 45°with respect to the longitudinal axis.…”
Section: Introductionmentioning
confidence: 99%
“…A miniature version of the shear-compression specimen was used for the characterization of nanomaterials. The modified shear-compression specimen was presented in [20]. In the modified specimen, the two diametrically machined gauges were semi-circular (instead of rectangular).…”
Section: Introductionmentioning
confidence: 99%